Analysis of Factors Hindering DPIB Students’ Adaptation to the Implementation of Building Information Modeling at SMKN 6 Bandung - Robi Rohendi; Abyan Fathoni Ridzkiyo; Hani Safitri; Nurafifah Dwi Rizqi Prasetyo; Wardah Aprilia Ningrum (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2026)
Building Information Modeling (BIM) implementation in vocational education in Indonesia, especially in vocational schools, faces significant challenges such as technology gaps, technical complexity of BIM systems, and limited supporting facilities. This study aims to analyze the inhibiting factors of BIM adaptation in students majoring in Building Information Modeling Design (DPIB) at SMKN 6 Bandung using a descriptive quantitative method. Evaluations were conducted on facilities, student readiness, curriculum, teacher learning methods, and external support. The results of this study indicate that (1) facilities are the main obstacle due to limited infrastructure (hardware/software) and practice space; (2) student readiness is disrupted by low digital literacy and dependence on teachers; (3) the curriculum is not yet responsive to industry needs, (4) teacher learning methods use a passive approach that contradicts the principles of constructivism; and (5) external support is incidental. Thus, BIM integration requires a holistic approach, namely improving facilities, project-based curriculum, teacher training, and strategic partnerships. These solutions are important to achieve effective BIM integration to bridge the gap between graduate competencies and industry needs.